Efektivitas Video Micro-Learning terhadap Pemahaman Biokimia pada Mahasiswa Kedokteran - Zahara Nurfatihah Z; Syazili Mustofa (KOLONI, 2026)
High remediation rates in Biochemistry examinations at the Faculty of Medicine, Universitas Lampung underscored the need for supplementary digital learning media. This study aimed to evaluate the effectiveness of short video-based micro-learning in improving Biochemistry comprehension among medical students. An experimental one-group pretest posttest design was employed involving 188 paired data records from the students enrolled in Biochemistry 2. An animated video of approximately seven minutes was uploaded to YouTube and made accessible one day before each face-to-face session. Comprehension was assessed using ten multiple-choice questions administered before and after the intervention. Shapiro-Wilk testing confirmed non-normal score distributions in both assessments, warranting the Wilcoxon Signed-Rank test. Mean scores increased significantly from 81.76 ± 21.29 to 96.44 ± 9.05 (W = 272.5, p < 0.001; Cohen's d = 0.735), indicating a large effect size. The passing rate rose from 77.1% to 98.9%, accompanied by a marked narrowing of score variance, reflecting reduced comprehension disparity among students. The score distribution shifted markedly, with the proportion of students achieving scores in the 90–100 range increasing from 55.9% to 94.1%. These results support the view that learning through a combination of visual and auditory is more effective in building comprehension than methods relying on a single sensory. These findings demonstrate that short video micro-learning constitutes a supplementary strategy capable of substantially improving Biochemistry comprehension and reducing remediation rates in medical education.